(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: Studies have shown that the risk profile of cardiovascular diseases for women of reproductive age is not the same as that of postmenopausal women. The risk profile of women of reproductive age group in our country has not been well studied. The present study was intended to investigate the risk profile and risk behaviour of reproductive age women for cardiovascular diseases. Materials and Methods: This cross-sectional study, intended to assess the risk factors of cardiovascular diseases among reproductive age women (ranging from 15 - 49 years), was conducted on women with cardiovascular diseases admitted at two selected Cardiac Specialized Hospitals of Dhaka city. A total of 223 women with predefined eligibility criteria were included in the study. The study investigated the details of the socio-demographic, behavioural, anthropometric and biochemical characteristics of the sampled population. Result: More than two-fifth of the respondents belonged to age group 35-45 years. A few (1.3%) respondents were currently smoker. But over 8% were used to consuming smokeless tobacco (betel-nut with zorda, gul etc.) and 12.6% were occasional consumer. The mean duration of smokeless tobacco consumption was 14.1 ± 10.6 years and the mean frequency of consumption of smokeless tobacco was 3.6 ± 2.3 per day. More than one-third of the respondents (35.90/0) were overweight and 15.7% were obese. The mean BMI of the respondents was 23.8 ± 4.8 kg/m2. The mean waist and hip circumferences were 98.9 ± 17 and 99.9 ± 12.2 cm respectively. Majority (89.7%) of the women’s waist:hip ratio was at risk. The recommended fruit and vegetables intake (at least 5 servings a day) by the respondents was not found at all. Over half (50.2%) of the respondents were used to regular intake of extra table salt in their meals, 19.3% were occasional user. Nearly one-fifth of the respondents (17.9%) used to have fast food and the mean number of intake was 1.5±1 per day in a usual week. Over one-quarter (27.4%) of the respondents reported maintaining recommended physical exercise (minimum 30 min of physical exercise for at least 5 days a week). About 40% were hypertensive. Nearly two-thirds (62.3%) had the family history of chronic diseases; of them approximately 55% reported hypertension, 51.4% heart disease and diabetes mellitus. Conclusion: The women in general took inadequate fruits and vegetables. One-third of women were accustomed to fast food, street food, fatty-food etc. Every 1 in 16 women was used to consuming smokeless tobacco. Only one-third took recommended physical exercise. The rapidly increasing trend of obesity might be due to sedentary life-style with increased consumption of fatty-food and less intake of fruits and vegetables. Further investigation with large sample is recommended to validate the findings of the present study. Ibrahim Cardiac Med J 2014; 4(2): 10-15